Attention Bias to Emotional Faces in Depressed People1 - bita ajilchi; hasan ahadi (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2013)
Background and Objective: Recent studies show that depressed people have an attention bias to negative stimuli. Therefore, the present study was carried out to compare attention bias in depressed and normal people. Method: The present research was an analysis study with a causal- comparative method. The statistical population included all the depressed individuals who had referred to a psychological clinic in Tehran. Using convenience sampling method and carrying out the Beck Depression Inventory as well as the unstructured interview with DSMIV criteria, 30 depressed individuals (cut-off point 21 and higher) were selected as the patient group, and then were compared to 30 normal people, as the control group, in terms of sex, age, marriage status, and education levels as compare group. Finally, the computer-based neurological test of Dot- Probe (emotional faces stimuli) was performed on the subjects of both groups. Results: The data were analyzed using t-test to examine the extent of matching between the two groups, and the multivariate analysis of covariance (MANOVA) was applied to study attention bias in the two groups. The results showed that there was a difference of time speed between the two groups; i.e. the depressed group acted slower in responding to incongruent stimuli. However, there was no significant difference in accuracy of the responds. Conclusion: The findings imply the role of depression severity in exacerbating attention bias in depressed people, and also the necessity to apply treatment methods or to use attention bias modification in depressed individuals